2013
DOI: 10.1007/s11060-013-1320-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear distortion correction of diffusion MR images improves quantitative DTI measurements in glioblastoma

Abstract: The purpose of this study was to use a retrospective nonlinear distortion correction technique and evaluate the changes in DTI metrics in areas of interest in and around GBM tumors. A total of 24 histologically confirmed GBM patients with pre-operative 20-direction DTI scans were examined. Variability in apparent diffusion coefficient (ADC) and fractional anisotropy (FA) in normal tissue before and after distortion correction were examined. Changes in mean, median and variance of ADC and FA in contrast enhanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
7
1
Order By: Relevance
“…Additionally, image distortions on diffusion MR images obtained using echo planar imaging may have led to inaccuracies when estimating the ADC characteristics within the contrast-enhancing lesion. Estimates of ADC L , however, have been shown to be relatively robust even in the presence of distortion (30) and results from the current study suggest a COV of only 2.5%, suggesting image distortion may not have been a critical limitation. Additionally, more in-depth baseline characteristics, including information about post-progressive treatment and molecular information, were not available for the trials used in the current study.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Additionally, image distortions on diffusion MR images obtained using echo planar imaging may have led to inaccuracies when estimating the ADC characteristics within the contrast-enhancing lesion. Estimates of ADC L , however, have been shown to be relatively robust even in the presence of distortion (30) and results from the current study suggest a COV of only 2.5%, suggesting image distortion may not have been a critical limitation. Additionally, more in-depth baseline characteristics, including information about post-progressive treatment and molecular information, were not available for the trials used in the current study.…”
Section: Discussioncontrasting
confidence: 53%
“…Goodness of fit was determined to be adequate if the adjusted R 2 > 0.7. This approach is similar to those used previously (1820, 30). …”
Section: Methodsmentioning
confidence: 80%
“…In our model, despite the incompatibility of major histocompatibility complex (MHC), we observed the development of a tumor mass in immunocompetent mice inoculated with human GBM cells. MRI analysis of xenografted mice showed a growing tumor mass (Additional file 1 ) which enhanced with MR contrast, evidencing, BBB disruption (Figure 1 ), and the presence of necrotic/hemorrhagic spots in the core of the tumor mass, similar to what is described in GBM patients [ 10 ]. Moreover, we also observed the same histopathological features present in GBM patients [ 9 ] as described by the WHO (Figure 2 ).…”
Section: Discussionsupporting
confidence: 52%
“…In addition, GBM is one of the most angiogenic tumors [ 7 , 8 ]. The presence of glomeruloid vessels is an important feature for diagnosis through histopathological analysis, as well as cellular atypia, necrosis, and mitotic figures [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another potential limitation was the potential influence of geometric distortions on ADC measurements. Woodworth et al ( 20 ) recently showed that post hoc non-linear distortion correction of diffusion MR images to high-resolution T2-weighted images can improve diffusion measurements in brain tumors, demonstrating that subtle distortions can cause significant differences in ADC measurements. A similar approach could have been used in the present study to improve ADC measurements, even in patients with usable data (QC ≥3).…”
Section: Discussionmentioning
confidence: 99%